LITERATURE REVIEW ON AI-DRIVEN PERSONALIZED LEARNING AND GAMIFICATION IN PROGRAMMING EDUCATION. - Bouallegue, Seifeddine; Omri, Aymen; Khan, Shiban; Shikfa, Abdullatif; Ciftler, Bekir Sait; Al-Naemi, Salem (Scientific Culture, 2026)
Programming education has become vital in university curricula, providing students with critical thinking and problem-solving skills essential for innovation and adapting to new technologies. However, the abstract nature of programming concepts can lead to a lack of motivation among students, making it challenging to learn effectively. Gamification has emerged as an effective solution to enhance student motivation and engagement, while AI-driven personalized learning techniques offer the potential to further amplify these benefits. This literature review examines related works on AI-driven personalized learning and gamification in programming education. We analyze various techniques and methods introduced in the field, along with performance metrics used to assess their effectiveness. We identify potential future directions and open problems based on our findings, aiming to guide further research and implementation strategies in this area.